Nerve ultrasound in clinical management of carpal tunnel syndrome in mucopolysaccharidosis. (21st April 2016) - Bäumer, Tobias; Bühring, Nina; Schelle, Thomas; Münchau, Alexander; Muschol, Nicole
Abstract : Aim: Mucopolysaccharidoses (MPS) are a group of diseases with an almost 100% lifetime incidence of carpal tunnel syndrome (CTS) in MPSsubtypes I, II, and VI. We compared nerve ultrasound with clinical signs and electrophysiology in a clinical setting to screen for CTSin MPS. Method: Twenty‐four patients (13 male, 11 female, mean age of 7y 11mo [SD8y 5mo], range 6mo–29y) were screened for CTS. Eight of these patients were re‐examined post‐operatively. Clinical signs, distal motor latency, compound muscle action potential, sensory nerve action potential amplitude and velocity, as well as echogenicity and the cross‐sectional area (CSA) of the median nerve at the wrist and forearm determined with ultrasound were assessed and the wrist to forearm ratio (WFR) calculated. Eighteen healthy participants formed a comparison group, who were also investigated with nerve ultrasound. Results: In 26% of the patients' hands, clinical signs of CTSwere present; 77% fulfilled electrophysiological and 92% nerve ultrasound criteria for CTS. Post‐operatively, electrophysiology improved significantly, whereas ultrasound results were unchanged. In the comparison group, age and height correlated with the CSA, but not with WFR. Interpretation: Nerve ultrasound is a useful and painless primary screening tool for CTSin MPS. What this paper adds: Nerve ultrasound is a highly sensitive tool for detecting carpal tunnel syndrome (CTS) in mucopolysaccharidoses (MPS). Nerve ultrasound appears to be more sensitive than clinical signs and electrophysiology for detecting CTS in MPS. Electrophysiology is more sensitive than nerve ultrasound to detect post‐operative changes in CTS in MPS Combining electrophysiology and nerve ultrasound for screening and follow‐up before and after surgery for CTS in MPS is more sensitive than each method alone. This article is commented on by Jester on page1104 of this issue.